TRAUMA EXPOSURE, EMOTION REGULATION, AND NEUROTICISM AS PREDICTORS OF SLEEP QUALITY AMONG MILITARY PERSONNEL AT ARMED FORCES COMMAND AND STAFF COLLEGE (AFCSC), JAJI - Odoh, Priscilia Ogechukwu; Gandi, Joshua Chiroma; Ogboji, Chukwuebuka Emmanuel (African Journal of Social and Behavioural Sciences, 2025)
This study explored how trauma exposure, emotion regulation, and neuroticism predict sleep quality among military personnel at the Armed Forces Command and Staff College (AFCSC), Jaji, Nigeria. Using a cross-sectional survey, data were collected from 291 commissioned officers across the Army, Navy, and Air Force through standardized psychological instruments. Data was analyzed using Multiple Hierarchical Regression. Findings revealed that trauma exposure had the most substantial influence on poor sleep quality (β = .62, p < .001), followed by expressive suppression (β = .48, p < .001) and neuroticism (β = .18, p < .001). Surprisingly, cognitive reappraisal, often regarded as an adaptive strategy, was also associated with poor sleep (β = .37, p < .001), suggesting that prolonged cognitive effort under chronic stress may worsen sleep disturbance. The combined influence of the predictors explained a large proportion of the variance in sleep quality, indicating that sleep dysfunction in the military extends beyond physical fatigue to include psychological strain and maladaptive coping. It was concluded that trauma exposure, emotion regulation style, and personality factors jointly shape sleep health in high-stress occupational settings. Therefore, military health programs should incorporate trauma-informed counselling, adaptive emotion regulation training, and personality-based resilience interventions to enhance sleep quality and overall psychological well-being among Nigerian military personnel.